Osteonecrosis as a post-surgical complication in oral surgery in patients undergoing antiresorptive treatment. Integrative review (Research, Society and Development, 2023)
Currently, the administration of antiresorptive drugs for the treatment of different diseases related to bone tissue has been increasing. However, they can also trigger complications that we as health professionals should be aware of. Today there is a lot of information about the subject, for this reason, it is important that we have more relevant and concrete information that is easy to understand for a general practice dentist to detect this affectation early, assessing the risks and benefits that such treatments entail, the objective of the This review is to make a comprehensible synthesis of the most important aspects of osteonecrosis of the jaw related to antiresorptive drugs and the care to be taken into account. A thorough search was carried out in different databases: Pubmed, EBSCO, Science Direct, Scopus, Scielo. Being included 27 articles from 2019, 1 base article, 1 clinical guide and 1 book for the present review. Osteonecrosis is a complication that can appear after the administration of antiresorptive drugs such as bisphosnates and denosumad used in the treatment of bone diseases. Those administered intravenously have been reported mostly with the development of this complication, among the triggering local risk factors. extractions predominate. The multidisciplinary approach is essential for early recognition of predisposing patients, providing timely and preventive care to reduce the severity of this complication.